Microsatellite genotyping of medieval cattle from central Italy suggests an old origin of Chianina and Romagnola cattle - Gargani, Maria; Pariset, Lorraine; Lenstra, Johannes A.; De Minicis, Elisabetta; , European Cattle Genetic Diversity Consortium; Valentini, Alessio (Frontiers in Genetics, 2015)
Analysis of DNA from archaeological remains is a valuable tool to interpret the history of ancient animal populations. So far most studies of ancient DNA target mitochondrial DNA (mtDNA), which reveals maternal lineages, but only partially the relationships of current breeds and ancient populations. In this study we explore the feasibility of nuclear DNA analysis. DNA was extracted from 1000-years old cattle bone collected from Ferento, an archaeological site in central Italy. Amplification of 15 microsatellite FAO-recommended markers with PCR products yielded genotypes for four markers. Expected heterozygosity was comparable with values of modern breeds, but observed heterozygosity was underestimated due to allelic loss. Genetic distances suggested a position intermediate between (1) Anatolian, Balkan, Sicilian and South-Italian cattle and (2) the Iberian, North-European and Central-European cattle, but also a clear relationship with two central-Italian breeds, Chianina and Romagnola. This suggests that these breeds are derived from medieval cattle living in the same area. Our results illustrate the potential of ancient DNA for reconstructing the history of local cattle husbandry.